The Redactional Agenda of the Book of Psalms - Crutchfield, John C. (Hebrew Union College annual, 2003)
Scholars are currently paying increased attention to the literary shape of the final form, or the redactional agenda, of the Book of Psalms. This article seeks to evaluate the most prominent of these proposals. Some proposals emphasize the nation's disappointment surrounding the failure of the office of Davidic king; others, wisdom motifs prominent during intertestamental times. Still others see eschatology as the redactional focal point. The author examines these proposals and concludes that they all have legitimate contributions to make to the study of the Hebrew Psalter. The problem with most of these proposals is that they are mutually exclusive, and therefore cannot benefit from the insights of other proposals. The author suggests that the main themes of the Hebrew Psalter are wisdom (right living, eschatology (the messiah in the eschaton), and worship (adoration of God for his person and works). These three themes are all emphasized by the prominent placement of psalms that deal with their respective subjects as well as by repetition of the various themes throughout the book. Part of the interpreter's task is to understand a given psalm in light of the overall thematic concerns of the Book of Psalms as a whole.